2019
DOI: 10.1016/j.appet.2019.01.025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of food type on the portion size effect in children aged 2–12 years: A systematic review and meta-analysis

Abstract: This is a repository copy of The effect of food type on the portion size effect in children aged 2-12 years: A systematic review and meta-analysis..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 65 publications
(139 reference statements)
3
23
0
2
Order By: Relevance
“…Our findings show that the PSE is apparent in children consuming unit-based foods, and supports recent systematic review evidence demonstrating the PSE in both unit and amorphous (foods without a distinct shape or form) foods in children aged 2–12 years [54]. Visual cues, such as the shape of food and how it is presented on a plate, together with social norms, contribute an important role in how much an individual consumes [55,56,57].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings show that the PSE is apparent in children consuming unit-based foods, and supports recent systematic review evidence demonstrating the PSE in both unit and amorphous (foods without a distinct shape or form) foods in children aged 2–12 years [54]. Visual cues, such as the shape of food and how it is presented on a plate, together with social norms, contribute an important role in how much an individual consumes [55,56,57].…”
Section: Discussionsupporting
confidence: 90%
“…The design, including the natural childcare setting and use of familiar and commonly consumed lunch-time foods [36,38], are strengths of this study. Furthermore, incorporating a popular and typical unit-based HED main food in the meal, and controlling the unit numbers of this food strengthens the evidence of the PSE to include unit as well as amorphous type foods [54], and highlights the potential role of unit bias on pre-school aged children’s eating practices. A limitation of the present study was the lack of a dietary follow-up to monitor intakes beyond a single meal.…”
Section: Discussionmentioning
confidence: 89%
“…Experiments show that young children are susceptible to consuming more when served larger portion sizes 37 . However, parents tend to be more concerned about feeding young children enough and a variety of food rather than too much 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Research also showed the influence of the presence of other children on the level of food consumption: preschool children ate more pizza in groups of nine than in groups of three individuals (Lumeng and Hillman 2007). At this age children become sensitive to portion size, meaning that they eat more when larger food portions are presented to them (Reale et al 2019).…”
Section: The Preschool Age: a Neophobic Phase Source Of Family Tensionsmentioning
confidence: 99%